The Developing Of Children's Stories In Strengthening The Educational Characters Of Primary School Student's Nationalism - Werdiningsih Werdiningsih; Ida Zulaeha; Ani Rusilowati (International Conference on Science, Education, and Technology, 2022)
Problems with the elementary students ranging symptoms less love my homeland and a sense of national spirit because at least value-laden storybooks patriotism and national spirit. The research objective is developing story book children with patriotism and national spirit. The research is research and development (R&D).The development test consists of testing experts, limited-trials, and scale test. Characteristics of the data are analyzed by analysis needs. Data analyzed with descriptions percentage, ANOVA and N-gain. The hypothesis testing used one sample t-test. The calculation of the results of one sample t-test showed the price t count> t table so that Ha is accepted. The results showed the characteristics of the story book children is appreciated, communicative, motivation, understanding, beauty, and balance. Characteristics of effectiveness of teaching reading in the study material obtained completeness 97.5% ≥ 70%, increasing to 0.55 with N-gain medium category. Observations as a character on stage entrenched affective domain (MK), mean learning outcomes experimental class is larger than the mean control class learning outcomes, and the results of the ANOVA calculations there are significant. Acceptability of a children's book laden with patriotism and national spirit for teachers get the score of 91.25% and 91.94% of students score in very acceptable.